2022
DOI: 10.1021/acs.macromol.2c01069
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Hydrogen Bonds of Nucleobases Enable Programmable Morphological Transformations of Mixed Nanostructures

Abstract: Biological systems enable the efficient implementation of various functions by segregating responsive biomacromolecules or assemblies in disparate compartments, which is highly fascinating and desired by materials scientists. However, it is still challenging to elegantly modulate the responsive behaviors of mixed assemblies in synthetic polymeric systems owing to the lack of delicately responsive nanostructures. Herein, bioinspired complementary hydrogen bonding interactions of nucleobases are harnessed to ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…When the aspect ratio, that is, N BB /N SC , where N BB is the degree of polymerization (DP) of the backbone and N SC is the DP of side chains, is sufficiently high, MBBs exhibit cylindrical conformations, 1–6 resembling bottlebrush flowers and brushes for bottles and pipes. Brush polymers have attracted considerable interest in recent years, from synthesis to study of structures and assemblies; 7–22 many unique characteristics have been revealed, such as large and tunable persistence length, no backbone entanglements, and unusual crystal habits. 1–25 A variety of potential applications of MBBs have been demonstrated, ranging from photonic crystals to drug delivery systems, lubricants, and emulsion stabilizers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the aspect ratio, that is, N BB /N SC , where N BB is the degree of polymerization (DP) of the backbone and N SC is the DP of side chains, is sufficiently high, MBBs exhibit cylindrical conformations, 1–6 resembling bottlebrush flowers and brushes for bottles and pipes. Brush polymers have attracted considerable interest in recent years, from synthesis to study of structures and assemblies; 7–22 many unique characteristics have been revealed, such as large and tunable persistence length, no backbone entanglements, and unusual crystal habits. 1–25 A variety of potential applications of MBBs have been demonstrated, ranging from photonic crystals to drug delivery systems, lubricants, and emulsion stabilizers.…”
Section: Introductionmentioning
confidence: 99%
“…Brush polymers have attracted considerable interest in recent years, from synthesis to study of structures and assemblies; 7–22 many unique characteristics have been revealed, such as large and tunable persistence length, no backbone entanglements, and unusual crystal habits. 1–25 A variety of potential applications of MBBs have been demonstrated, ranging from photonic crystals to drug delivery systems, lubricants, and emulsion stabilizers. 26–37…”
Section: Introductionmentioning
confidence: 99%
“…Nucleobase-containing polymers as DNA analogues incorporate polymers polymerized from nucleobase-containing monomers or postmodified with nucleobase functionalities, garnering tremendous interest. , In contrast to DNA, nucleobase-containing polymers possess many prominent advantages such as structural diversity, facile scalability, low synthetic costs, and tunable properties. As a result, robust bioplastics and strong adhesives can be fabricated by rationally designing nucleobase-containing polymers. Importantly, specific hydrogen-bonding interactions between complementary nucleobase-containing polymers can be harnessed to enhance and modulate the relevant properties. Meanwhile, the hydrogen-bonding interaction between complementary nucleobase-containing monomers and polymers is also feasible to achieve template polymerization. Both nucleobase-containing macromolecule–macromolecule and macromolecule–monomer interactions also exist in DNA, but the nucleotide–nucleotide interaction is not observed for DNA owing to the weak bonding energy in aqueous environments.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, natural materials such as nacres or bones are strong and tough nanocomposites consisting of proteins and minerals based on supramolecular chemistry. , The fast dissociation and reformation of supramolecular interactions dissipate and transfer concentrated stress with much higher efficacy. Recently, the supramolecular hydrogen bonding (H-bonding) between complementary nucleobases in nucleic acids has been harnessed to bestow bioplastics or adhesives with robust properties. Meanwhile, nucleobase-containing synthetic polymers and materials have been widely exploited to mediate polymer tacticity, to control nanostructured morphologies, and to template polymerizations. Considering the specificity and selectivity of H-bonding between complementary nucleobases, elaborate interfacial interactions based on nucleobases are highly expected to enable the fabrication of robust polymer nanocomposites.…”
Section: Introductionmentioning
confidence: 99%